Total‐evidence backbone phylogeny of Aleocharinae (Coleoptera: Staphylinidae). (18th December 2020) - Orlov, Igor; Leschen, Richard A.B.; Żyła, Dagmara; Solodovnikov, Alexey
Abstract: Phylogenetic studies of Aleocharinae rove beetles, arguably one of the least known and the largest insect lineages, are compromised by its enormous taxonomic diversity. DNA, a powerful resource for phylogenetics, is not available for numerous extant aleocharine species. We provide a broad comparative morphological study of Aleocharinae to frame molecular datasets for total‐evidence analyses. Using full‐body dissections and slide‐mounting techniques for light microscopy supplemented by scanning electron microscopy, we constructed a morphological matrix across all major taxa focused on non‐inquiline tribes of Aleocharinae and outgroups. Phylogenetic analyses of this matrix concatenated with earlier published DNA loci and including exemplar taxa lacking molecular data, resolved outstanding controversies and, among other novelties, showed that: the Habrocerinae + Trichophyinae clade is sister group to Aleocharinae; Hypocyphtini are sister to the rest of the "higher Aleocharinae"; Taxicerini are sister to Aleocharini; Hoplandriini and Placusini are nested within a polyphyletic Oxypodini; Hoplandriini are sister to Meoticina; and Actocharini are nested within Liparocephalini. For the first time, morphological synapomorphies are identified for some large clades of Aleocharinae. In addition, 1252 high‐resolution microphotographs of aleocharine structures are made available online with the entire matrix for future research.